Three new cricket species and a new subgenus of Endecous Saussure, 1878 (Grylloidea: Phalangopsidae) from caves in northeastern Brazil - Carvalho, Pedro Henrique Mendes; Junta, Vitor Gabriel Pereira; Castro-Souza, Rodrigo Antônio; Ferreira, Rodrigo Lopes (Zootaxa, 2023)
The genus Endecous (Orthoptera, Grylloidea, Phalangopsidae), commonly found in caves, comprises more than 20 species, grouped into three subgenera: E. (Endecous), E. (Pedroecous) and E. (Notendecous). In this study, from differences observed mainly in the male genitalia, we describe a new subgenus—Endecous (Ramalhoecous) n. sp.—as well as three new species—E. (R.) infernalis n. sp., E. (E.) zin n. sp. and E. (E.) zaum n. sp.—all of them collected in caves in the Serra do Ramalho region, Northeastern, Brazil. We also briefly discuss some troglomorphisms verified in one of the new species: E. (R.) infernalis n. sp.